The Analysis of Covid-19 Knowledge of Health Sciences Students Based on Their Characteristics - Widowati, Retno; Indrayani, Triana; Rukmaini, Rukmaini (STRADA : Jurnal Ilmiah Kesehatan, 2020)
A total of 538 people were respondents in this study. The median knowledge of respondents was 37 and 71% of respondents had good knowledge. Respondents came from Nursing, Midwifery and Nursing Professional Education study programs. As many as 61.3% of students work as health workers. The respondent's province of residence consists of 19 provinces in Indonesia. Respondents aged <20 years to> 40 years, most 45.7% aged 20-25 years. The three most common sources of information COVID-19 are the internet 37%, television 25.3% and superiors and colleagues at work 19.7%. Cumulative Achievement Index (IPK) between 3.0 - 3.5 is the most IPK of respondents (59.7%). Median knowledge scores 37 and 71% of respondents have good knowledge. There was a significant relationship (p <0.05) between COVID-19 knowledge and the student's employment status, study program and health science student age.